ORGANIC FERTILIZER PRODUCTION USING BANANA PEEL, EGGSHELLS, AND YEAST: EFFECTS ON AMARANTHUS GROWTH - Aliyu, Muzzammil; Abdulmalik , Zaharadeen; Bako, Ziya’ulhaq Mukhtar; Jega, Rilwanu Muhammad; Kareem, Wasiu (FUDMA Journal of Sciences, 2024)
The use of organic fertilizers as an alternative to inorganic fertilizers is one way to reduce the use of inorganic fertilizers, which have negative effects when used for a long time. Banana Peels, Egg Shells, and Yeast were utilized to generate an organic fertilizer in this study. Banana peel is high in biomass fibre, nitrogen, potassium, and phosphorus, all of which are essential components of organic fertilizer. Phosphate and calcium, which are essential for plant growth, are found in eggshells, while yeast serves as a catalyst in nutrient cycling and organic matter decomposition. This study used a Randomized Completely Block Design (RCBD), which consisted of 3 treatments with 3 replications. To evaluate the yield and growth performance of Amaranthus under different organic fertilizer combinations using Banana Peels, Eggshells, and Yeast. A multi-factor Duncan Multiple Range Test (DMRT) was applied after ANOVA to determine significant differences in treatments. The results indicate that the combination of Banana Peels, Eggshells, and Yeast significantly improved yield compared to the combination without Yeast. Treatment A (Banana Peels, Eggshells, and Yeast) consistently outperformed other treatments. After four weeks, Treatment A in Combination 1 (Banana Peels, Eggshells, and Yeast) achieved a mean leaf count of 32, compared to 26.33 in Treatment B (Banana Peels and Eggshells) and 15.00 in the untreated control (Treatment C). This represents a 62% higher yield compared to the corresponding treatment in Combination 2, which did not include Yeast. The addition of Yeast was crucial in boosting Amaranthus growth, contributing to improved nutrient...
Keywords: Organic Fertilizer; Banana Peel; Eggshells; Yeast; Plant Growth